Hakluyt's promise an Elizabethan's obsession for an English America - Mancall, Peter C. 1959- (Yale Univ. Press, 2007)
"Hakluyt's Promise demonstrates [Hakluyt's] prominent role in the establishment of English America as well as his interests in English opportunities in the East Indies. The volume presents nearly fifty illustrations - many unpublished since the sixteenth century - and offers a fresh view of Hakluyt's milieu and the central concerns of the Elizabethan age"--Dust Jacket.
Keywords: Hakluyt, Richard <1552?-1616>; Hakluyt, Richard -- 1552-1616; Geschichte 1534-1614; Klerus; Clergy -- England -- Biography; Discoveries in geography -- English; Travel writers -- England -- Biography; Voyages and travels -- Early works to 1800; Entdeckungsreise; Engeland; Nordamerika; North America -- Discovery and exploration -- British -- Early works to 1800; Biografie